EVENT MARKETING TOKOPEDIA WIB TV SHOW X BTS ON PURCHASE INTENTION OF INDOMILK MILK PRODUCT, BANANA VARIANT - Muhammad Rizki Budimansyah; Arry Widodo (Jurnal Riset Bisnis dan Manajemen, 2021)
This research is motivated by the occurrence of the Covid-19 pandemic in Indonesia and the very rapid development of the Hallyu phenomenon during the quarantine period at home and the PSBB which is used by e-commerce to carry out promotional activities. The Covid-19 pandemic has made almost all business activities in Indonesia have a bad impact until bankruptcy. This forces companies to be able to find ways to survive during the pandemic and also compete with competitors.This study aims to determine and analyze the effect of the Tokopedia WIB BTV Show X BTS marketing event on the purchase intention of the Banana Flavored Indomilk Dairy Product. The method used is quantitative with the aim of causality research and the SEM-PLS analysis method. The sampling technique used is non-probability sampling with a total of 385 people throughout Indonesia who know and have seen the Tokopedia WIB TV Show marketing event. Based on the research hypothesis testing, it is concluded that event marketing directly has a positive and significant effect on buying interest.